Mapping Multi-Sensory Brand Experiences and Their Impact on Customer Satisfaction: A Bibliometric and Systematic Literature Review on Scopus - Silmi, Kevin Ghulaman; Budi Eko, Budi Eko Soetjipto; Ludi Wishnu, Ludi Wishnu Wardhana (PT. Maju Malaqbi Makkarana, 2025)
Multi-sensory brand experience has emerged as a crucial factor in modern marketing, significantly influencing customer satisfaction, brand perception, and loyalty. Despite its increasing importance, research in this area remains fragmented, with theoretical integration and empirical validation gaps. This study employs a Systematic Literature Review (SLR) and bibliometric analysis using the Scopus database to map the evolution of research on multi-sensory brand experiences and their impact on customer satisfaction. From an initial dataset of 203 documents, a rigorous selection process resulted in 41 relevant articles for in-depth analysis. Using VOS viewer, the study visualizes research networks, inter-topic relationships, and emerging trends, revealing a 47% increase in publication volume from 2012 to 2024. Findings indicate that customer satisfaction, consumer behaviour, and sales are dominant themes, with sentiment analysis and digital technology (AI, AR) gaining traction in recent years. However, significant gaps remain, particularly in experimental studies quantifying the long-term impact of multi-sensory experiences on customer loyalty and cross-industry comparisons of multi-sensory branding effectiveness. The novelty of this study lies in its combined bibliometric and systematic approach, which identifies critical research trends, theoretical gaps, and emerging digital strategies in multi-sensory marketing. This study contributes to the academic discourse by comprehensively synthesizing research trends and proposing future research directions in technology-driven branding strategies and consumer engagement.